An Experimental Study on the Performance of Check Valve-Aided Savonius Wind Rotors with Semi-Circular Blade - Ivan Farozan; Yuli Setyo Indartono (International Journal of Technology)
The Savonius wind turbine is perceived favorable for a small-scale application because it is simple, relatively inexpensive, insensitive to wind directions, and has a good self-starting ability. However, it has a low power coefficient caused by the negative torque from the returning blade. This study aimed to investigate the effect of valve addition on the semi-circular Savonius rotor's performance. The experiments for this study were conducted on an open jet wind tunnel, with the valve located near the rotation axis, blade center, and rotor tip. The valve opening area ratio used was 0.02, 0.04, and 0.06, with Reynolds numbers 73,000, 86,000, and 99,000. The results showed that rotors with a valve placed near the tip performed better than those at the blade center and near the rotation axis. The performance decreased with an increase in the valve opening area ratio. Furthermore, the performance-improvement magnitude decreased with an increase in the Reynolds number. The rotor with a single valve near the tip performed the highest at a Reynolds number of 73,000. It achieved a maximum power coefficient of 0.199 compared to 0.183 obtained by a conventional Savonius rotor.